2020
DOI: 10.1002/ange.202004248
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking Nature's Biosynthetic Power—Metabolic Engineering for the Fermentative Production of Chemicals

Abstract: Fermentation as a production method for chemicals is especially attractive, as it is based on cheap renewable raw materials and often exhibits advantages in terms of costs and sustainability. The tremendous development of technology in bioscience has resulted in an exponentially increasing knowledge about biological systems and has become the main driver for innovations in the field of metabolic engineering. Progress in recombinant DNA technology, genomics, and computational methods open new, cheaper, and fast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 132 publications
0
8
0
Order By: Relevance
“…Despite recent progress in fermentative processes, production of commodity chemicals by sugar fermentation remains difficult to scale 52,53 . Only a few examples have reached industrial level, including 1,3-propanediol, 1,4-butanediol, isobutanol, farnesene, lactic acid and succinic acid-all of which required substantial financial for acetone biosynthesis enzymes (ThlA, yellow; CtfAB, green; Adc, blue) of ten selected combinatorial library strains: four strains across the production range (ranks 1, 14, 26 and 150 of 247) and six strains with fixed reference genes but different promoter combinations (mean ± 1 s.d.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite recent progress in fermentative processes, production of commodity chemicals by sugar fermentation remains difficult to scale 52,53 . Only a few examples have reached industrial level, including 1,3-propanediol, 1,4-butanediol, isobutanol, farnesene, lactic acid and succinic acid-all of which required substantial financial for acetone biosynthesis enzymes (ThlA, yellow; CtfAB, green; Adc, blue) of ten selected combinatorial library strains: four strains across the production range (ranks 1, 14, 26 and 150 of 247) and six strains with fixed reference genes but different promoter combinations (mean ± 1 s.d.…”
Section: Discussionmentioning
confidence: 99%
“…and human investment 54,55 . The economics of turning one commodity (sugar) into another commodity and operating in batch processing mode is challenging; even for high-yielding pathways, it requires extremely high productivities and titers 53 . In the case of acetone and IPA production from sugars, the maximum yield is 50% 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…599 Analyzing the whole synthetic route in a retro-biocatalytic approach will unlock the true synthetic potential of enzymes, that naturally act in reaction sequences, and will allow performance of the whole synthesis or reaction modules through "artificial metabolic cascades" ideally in one pot 62,553,556,557 or in a single host cell. 37 As can be seen in the review, the majority of examples of synthetic routes involve only a single biocatalytic step and various established chemical transformations. Here, the chances to include more enzymes in the overall pathway will increase with the increasing number of reactions developed, especially for C−C bond formation.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, API synthesis based on complex metabolites, such as the antiviral agent Tamiflu from shikimic acid 35 or the anticancer agent Taxol from taxadiene, 36 obtained by fermentation using engineered microorganisms needs special expertise in metabolic engineering and is therefore not within the scope of this review. 37 Furthermore, only examples that were applied on ideally at least several gram scale or where information on industrial application is available are included. Complementary reviews are suggested.…”
Section: Introductionmentioning
confidence: 99%